Old Unions and New Social Movements - Carroll, William; Ratner, R.S. (Labour/Le Travailleur, 1995)
Based on extensive study of union organizations and activists in Greater Vancouver, this article offers a two-fold critique of the thesis that "new social movements" have supplanted the labour movement as the key collective agents of change in late-modern societies. In the first section we briefly review the claims of new social movement theory and point to some of the analytic difficulties in positing a sharp distinction between "old" unions and "new" social movements. We then present comparative case studies of two pan-union labour organizations active in the Lower Mainland, followed by findings from in-depth interviews with activists in these groups, and comparisons between the political orientations of labour activists and those of activists in new social movements. We find evidence of a labour movement increasingly open to popular struggles outside its own immediate orbit, sensitive to the needs of diverse and marginalized constituencies, tactically prepared if not psychologically predisposed to yield a leading role in any such coalitions, and capable of grasping the connections between social movement activism and everyday life activities. The future of the labour movement very much depends on putting these political sensibilities into practice through a deepening of solidarity with other progressive movements — whose own futures are themselves implicated in labour's prospects.